1995
DOI: 10.1063/1.114995
|View full text |Cite
|
Sign up to set email alerts
|

Scanning tunneling microscopy based lithography employing amorphous hydrogenated carbon as a high resolution resist mask

Abstract: Amorphous hydrogenated carbon (a–C:H) is introduced as a constituent of a two–layer resist system for lithography with a scanning tunneling microscope (STM) operating in air. The resist is made up of a thin electron sensitive and chemically amplified top resist (≤50 nm) and a–C:H as a thick conducting and etchable bottom resist. In this setup the bottom resist acts as the counter electrode allowing in principle operation on insulating substrates. We show that it is possible to generate structures with high asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Most of these techniques take advantage of the spatial resolution of the electronic emission from a tip to locally expose ultrathin electron resists [367][368][369][370], such as self-assembled monolayers [371,372] or Langmuir-Blodgett films [373], or to directly modify the structure of the superficial layer [374][375][376][377], such as the oxygenation of hydrogenated silicon [378,379]. A few methods based on mechanically engraving a soft layer with the sharp atomic microscope tip have also been proposed [380].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these techniques take advantage of the spatial resolution of the electronic emission from a tip to locally expose ultrathin electron resists [367][368][369][370], such as self-assembled monolayers [371,372] or Langmuir-Blodgett films [373], or to directly modify the structure of the superficial layer [374][375][376][377], such as the oxygenation of hydrogenated silicon [378,379]. A few methods based on mechanically engraving a soft layer with the sharp atomic microscope tip have also been proposed [380].…”
Section: Introductionmentioning
confidence: 99%
“…AFM studies on these carbon films suggest that they may be useful as smooth coatings or etch masks for nanometer patterning with intrinsic roughness smaller than 0.1 m. 26,27 Mass spectroscopy and optical emission spectroscopy studies indicated that significant concentrations of unsaturated hydrocarbon species ͑e.g., C 2 H 4 , C 3 H 4 , C 4 H 4 , and C 6 H 5 ͒ and hydrogen are formed.…”
Section: Discussionmentioning
confidence: 99%
“…8) Fine lithography is possible using nanotube tips which have a high aspect ratio and small radius of curvature at the tip end. The polysilanes are different from the resist films examined so far such as SAL-601-ER7, 3) SAL-601, 4) poly(methylmethacrylane), 5) Si-CARL, 6) and siloxene 7) which are patterned by exposure to electrons followed by liquid developing.…”
Section: Introductionmentioning
confidence: 86%
“…[2][3][4][5][6][7] The advantages of the SPM lithography technique are the higher resolution and absence of radiation damage in the substrate to be patterned.…”
Section: Introductionmentioning
confidence: 99%